UNDRAINED SHEAR STRENGTH OF ARIAKE CLAY BY ELECTRONIC CONE PENETRATION TESTING - M. A. Rashwan; T. Koumoto (Lowland Technology International, 2007)
Evaluation of undrained shear strength ( ) of clay using laboratory tests usually faces serious problems due to large scatter caused by sample disturbance and different testing procedures. In this paper, the filtering equation which is expressed as function of the deformation modulus ( ) and excess pore water pressure ( ) is proposed as a simple equation and applied for 11 clay sites to drop the values those its soil are considered to be rather disturbed. The filtered selected values were compared to find fairly good agreement with the predicted by the electronic cone penetration testing data.